Dietary Risk Assessment of v-ATPase A dsRNAs on Monarch Butterfly Larvae - Pan, Huipeng; Yang, Xiaowei; Bidne, Keith; Hellmich, Richard L.; Siegfried, Blair D.; Zhou, Xuguo (Frontiers in Plant Science, 2017)
By suppressing the expression of genes with essential biological functions, in planta RNAi can negatively affect the development and survival of target pests. As a part of a concerted effort to assess the risks of RNAi transgenic crops on non-target organisms, we developed an in vivo toxicity assay to examine the impacts of ingested dsRNAs incurred to the monarch butterfly, Danaus plexippus (L.), an iconic eco-indicator in North America. To create the worst case scenario, the full-length v-ATPase A cDNAs from the target pest, western corn rootworm, Diabrotica virgifera virgifera, and the non-target D. plexippus were respectively cloned. A 400 bp fragment with the highest sequence similarity between the two species was used as the template to synthesize dsRNAs for the subsequent dietary RNAi toxicity assay. Specifically, newly hatched neonates were provisioned with leaf disks surface-coated with v-ATPase A dsRNAs synthesized from D. v. virgifera and D. plexippus, respectively, a control dsRNA, β-glucoruronidase, from plants, and H2O. The endpoint measurements included gene expressions and life history traits. The 2283 bp D. plexippus v-ATPase A cDNA contains a 99 bp 5’-untranslated region, a 330 bp 3’-untranslated region, and an 1851 bp ORF encoding 617 amino acids. The temporal RNAi study did not detect any impact to D. plexippus v-ATPase A expression by the assay days and treatments. This was reflected in the phenotypic impacts of dietary RNAi, in which both survival rate and development time were not affected by the uptake of ingested dsRNAs. These combined results suggest that D. plexippus larvae are not susceptible to dietary RNAi, therefore, the impact of transgenic RNAi plants on this non-target organism is, likely, negligible.